2010
DOI: 10.5799/ahinjs.01.2010.03.0033
|View full text |Cite
|
Sign up to set email alerts
|

The effects of iron deficiency anemia on the thyroid functions

Abstract: ÖZETAmaç: Bu çalışmanın amacı demir eksikliği anemisinin tiroid fonksiyonları üzerine etkisi ve demir tedavisi sonrası değişiklikleri belirlemektir. Gereç ve yöntem:Bu çalışma, 42 hasta ve 38 sağlıklı birey ile yapıldı. Demir eksikliği anemisi tanısı serum ferritin ve tam kan sayımı yapılarak kondu. Hasta grubunda tedavi öncesi ve iki aylık tedavi sonunda ve kontrol grubunda ise 12 saat açlıktan sonra kan örnekleri alınarak serbest triiyodotironin (ST3), serbest tiroksin (ST4), total triiyodotironin (TT3), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…8 The hemoglobin levels in the study by erdem found to be 13.3±1.3 while present study revealed 10.12±2.17 in Indian population. The mean age of the patients between 20-40 years is 29.82±7.26 while the mean age for the age for patients 41-65 years is 50.48±6.93.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…8 The hemoglobin levels in the study by erdem found to be 13.3±1.3 while present study revealed 10.12±2.17 in Indian population. The mean age of the patients between 20-40 years is 29.82±7.26 while the mean age for the age for patients 41-65 years is 50.48±6.93.…”
Section: Discussioncontrasting
confidence: 43%
“…7 As of late studies completed in human and creatures have recommended that iron lack can influence the thyroid hormone in digestion system and peroxidase chemical which is catalyzed starting strides of thyroid hormone combination is subjected to the iron. 8 Microcytic anemia for the most part credit to malabsorption of Iron and loss of Iron by menorrhagia, though, macrocytic frailty causes or prompts malabsorption of vitamin B12, folate, pernicious paleness and deficient nourishment. 9 Immune system resulting in hypothyroidism might be connected with signs or side effects of other immune system sicknesses, especially vitiligo, malevolent sickliness, Addison's infection, alopecia areata, also, sort 1 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Severe Iron deficiency may lower thyroid peroxidase activity and interfere with the synthesis of thyroid hormones [53,54]. The same results were illustrated by Gökdeniz et al (2010) [55] who reported that hormonal changes returned to normal values with Iron supplementation. Also, Soliman et al (2010) [56] found that total T3 (tT3) and total T4 (tT4) levels of anemic rats were significantly lower than normal control and tT3/tT4 ratio was significantly higher in group treated with (40 mg ferrous sulphate /kg diet) than normal control group.…”
Section: Resultsmentioning
confidence: 86%
“…Secondary and subclinical hypothyroidism were found in Iron deficiency anemia. Hormonal changes returned to normal values with Iron supplementation [55].…”
Section: Resultsmentioning
confidence: 90%
“…Iron deficiency negatively affects the immune system 16 , thyroid metabolism 17 and cognitive functions 18 . On the other hand, iron surplus is related to various pathological conditions such as cancer 19 , neurodegenerative diseases 20 , and damage of liver 21 and testicles 22 .…”
Section: Discussionmentioning
confidence: 99%